1988
DOI: 10.1002/ana.410240613
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle crashes in dementia of the alzheimer type

Abstract: To assess the occurrence and related features of motor vehicle crashes in patients with dementia of the Alzheimer type (DAT) we studied 30 patients who had been followed longitudinally and 20 healthy age-matched control subjects. Data were gathered from first-degree relatives who had lived with the subjects for the previous 5 years or more. Forty-seven percent of the DAT patients incurred at least one crash while they were driving, whereas only 10% of the control subjects had had a crash in the previous 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
2
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(157 citation statements)
references
References 14 publications
(1 reference statement)
8
146
2
1
Order By: Relevance
“…Drivers in the earliest stage of dementia may pose relatively little risk, but with disease progression, they will become increasingly dangerous to themselves and others, until they are no longer capable of driving. Crash data studies have demonstrated that drivers with dementia are 2 to 5 times more likely to be involved in a collision, compared with drivers with no dementia (18,22). Further, several studies have shown that individuals with dementia are most likely to be involved in crashes at intersections, (23,24) suggesting that more than one vehicle is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Drivers in the earliest stage of dementia may pose relatively little risk, but with disease progression, they will become increasingly dangerous to themselves and others, until they are no longer capable of driving. Crash data studies have demonstrated that drivers with dementia are 2 to 5 times more likely to be involved in a collision, compared with drivers with no dementia (18,22). Further, several studies have shown that individuals with dementia are most likely to be involved in crashes at intersections, (23,24) suggesting that more than one vehicle is involved.…”
Section: Discussionmentioning
confidence: 99%
“…44,50 Since this tool was not originally designed to assess cognitive function with respect to driving, the MMSE as a measure to assess driving performance lacks validity when used to assess patients falling between the extremes of cognitive impairment. 7,51 The Useful Field of View (UFOV) is a computer-administered test that measures and detects abnormalities in the speed of visual processing and sensory function. UFOV also measures skills in selective and divided attention.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…45,46,[56][57][58] These studies may be confounded because of the failure to control for the amount of mileage actually driven, lack of control groups, small sample size, method of reporting and avoidance of high risk driving situations. [44][45][46]51,59 Overall, the evidence does support an increased risk of motor vehicle collisions in patients with dementia even with restrictions attached to driving, such as driving distance or location. 51,60-62…”
Section: Collision Ratementioning
confidence: 97%
See 1 more Smart Citation
“…It is known that patients with Alzheimer's disease (AD) become unsafe drivers (e.g., Friedland et al, 1988;Rizzo et al, 2001;Rizzo et al, 1997;Tuokko et al, 1995). However, this diagnosis alone is not sufficient grounds for restricting driving privileges, as some patients in the early stages of this progressive condition may have only isolated memory deficits and may maintain driving ability comparable to their non-dementing peers.…”
Section: Introductionmentioning
confidence: 99%